Pavel Haas: “Janáček’s Most Talented Student” - Lubomír Spurný (Muzikološki Zbornik, 2015)
In  the  course  of  the  1920s  and  30s  Pavel  Haas (1899–1944) earned a reputation for himself in broader cultural consciousness as an original composer and Janáček’s “most talented student”. In the specific context of Czech music he likewise has the reputation of an innovator but is considered to have been strongly rooted in tradition as well.